Dampak Gangguan Muskuloskeletal Terhadap Integritas Jaringan Kulit dan Proses Penyembuhan Luka - Alicia Syifa; Alya Sagita; Andhini Saskia; Annisa Birrul; Aqila Widya; Assyifa Friska; Liss Dyah Dewi Arini (INDO PUBLISHING, 2025)
The musculoskeletal system and the integumentary system are two important systems in the human body that play a mutually supportive role in maintaining optimal body function. The musculoskeletal system consists of bones, muscles, and joints that function to support the body and enable movement, while the integumentary system, which includes the skin, hair, and nails, functions to protect the body from external factors. Disorders of the musculoskeletal system, such as immobilization due to injury or fracture, can have an impact on the integumentary system, especially in the form of pressure ulcers due to reduced blood flow to skin tissue. This study aims to understand the relationship between musculoskeletal disorders and skin tissue integrity and the wound healing process. The methods used include a literature review and physiological analysis through the LFM (Look, Feel, Movement) physical examination approach. The results of the study indicate that the prevention of pressure ulcers requires the role of nurses in maintaining mobilization, skin hygiene, and patient positioning. In conclusion, understanding the relationship between these two systems is important to support holistic nursing care and prevent complications in patients with mobility disorders.